NILAI TAMBAH PRODUKSI MOULDING DARI BEBERAPA PERUSAHAAN DI JAWA TIMUR DAN SUMATERA SELATAN - Sylviani Sylviani; Akub J Abdurachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Study about added value have done in relation with the diversification of wood working. Product of moulding Is one of the export product commondity which could contribute to increase foreign exchange earning. The obyective of the study is to conduct a study on several sawmills in South Sumatera and East Java.Average sawn timber waste and sawntimber that could be produce are 14. 600,50 cu. meter per industry each year. Those material which can be processed into moulding is 4.919, 75 cu. meter a year. Rendement of moulding that originated from sawntimber waste is less than 25 percent, and the one from sawn timber is 50 percent.The factory added value which yields profit is 226.863.832 rupiahs a year or 28.559 rupiahs per cu.m moulding. Income share distributed among of equipment factors are 34.273,50 rupiahs per cu.m (35,8 percent), labour 26.000 rupiahs per cu.m (27,2 percent), materials 6.892,50 rupiahs per cu.m (7,2 percent) and manager 28.559,02 rupiahs per cu.m (29,8 percent).Average employment opportunity to produce for each industri is 73.853 mandays or 516.973 manhours a year. Because the sawntimber waste and sawn timber was profitable to produce moulding, it is advisable that activities in the sawmills should be directed to produce moulding.